1998
DOI: 10.1177/021849239800600306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy on Long-Term Follow-Up of Mitral Valve Bioprostheses

Abstract: Between 1986 and 1990, 304 females between 11 and 45 (mean, 33.9 ± 6.9) years of age underwent isolated mitral valve replacement with a bioprosthesis. Thirty-nine of the 285 survivors experienced 48 pregnancies during the late follow-up period (group 1). Structural valve deterioration occurred in 25 (64.1%) of these patients and in 70 (28.4%) of the 246 patients (group 2) who did not become pregnant (p < 0.01). The mean time at which structural valve deterioration occurred was 7.01 ± 1.19 years postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In total, 16 studies were considered eligible for this meta-analysis, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 of which 1 study was included for subgroup analysis only because of overlapping population. 25 The individual study characteristics are listed in the Appendix E1 , Table E5 .
Figure 1 Flowchart of reference search, screening, and selection procedure.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 16 studies were considered eligible for this meta-analysis, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 of which 1 study was included for subgroup analysis only because of overlapping population. 25 The individual study characteristics are listed in the Appendix E1 , Table E5 .
Figure 1 Flowchart of reference search, screening, and selection procedure.
…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported on pregnant women with bioprosthetic mitral valves, encompassing a total of 155 pregnancies. 10 , 11 , 12 , 17 , 20 , 25 In total, 23 women (14.8%) received prophylactic anticoagulant therapy due to chronic atrial fibrillation. A total of 14 studies reported on patients with mechanical prostheses, encompassing a total of 613 pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations